Peripartum Hysterectomy and Analysis of Risk Factors - Basnet, Pritha; Rai, Rubina; Agrawal, Ajay; Thakur, Achala; Shrestha, Ramesh (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To determine the incidence and risk factors of women undergoing peripartum hysterectomy at BPKIHS, Dharan. Methods: A descriptive study was conducted for all women undergoing peripartum hysterectomy in two years from July 2012 to June 2014.Various maternal characteristics including demographic data, previous obstetric details, antepartum, intrapartum and postpartum data were collected and analysed. Results: There were 29 cases of peripartum hysterectomy among 19,539 births in 2 yrs (1.48 per 1000 births). Indications for peripartum hysterectomy were uterine rupture (65.5%), morbid adherence of the placenta (13.8%) and uterine atony (12.9%). Previous caesarean section was identified as independent risk factor with relative risk of 1.8 (95% CI 1.3-2.5, p< 0.003). Maternal morbidity was significant with febrile morbidity and urinary tract injury among the most common complications. Conclusions: Uterine rupture causing severe haemorrhage was the commonest indication for peripartum hysterectomy. Timely intervention reduces the peripartum maternal and perinatal morbidity and mortality.